Transcreation of advertising in international marketing as a way of giving new life to the original text - Księcikowska, Magdalena (The Art of Living, Surviving, Reviving. Studies in Linguistics. The 50th Anniversary of Romance Studies at the University of Łódź, 2022)
The article discusses the phenomenon of transcreation, a translation method used in the advertising industry as one of the stages in the development of an international advertising campaign. Transcreation is halfway between translation and the creation process from scratch, so it seems like a perfect solution to revive the original message in one new version. It is based on the adaptation of the original intent of the advertisement in order to obtain an equivalent reaction from the relevant public, taking into account the socio-cultural differences and nuances, linguistic peculiarities and habits of consumption of the target market. It stays true to the meaning of the original text, always trying to find creative ways to produce an authentic and compelling message to recipients that represent a different culture from that of the country of origin.